1998
DOI: 10.2307/3004051
|View full text |Cite
|
Sign up to set email alerts
|

Parenting from a distance: The effects of paternal characteristics on contact between nonresidential fathers and their children

Abstract: Changes in marital and fertility behavior have influenced the role of father for many men. We use data from the first two waves of the National Survey of Families and Households to examine various sociodemographic, situational, and attitudinal characteristics that might influence the degree of contact between nonresidential fathers and their minor children. We tap two different dimensions of distance parenting and find that although several variables influence both visiting and talking on the telephone or writ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
211
2
8

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(232 citation statements)
references
References 31 publications
11
211
2
8
Order By: Relevance
“…Some studies indicate that father sole custody is more common among previously married than previously cohabiting parents, and more common among parents who had been married for a long time than those who had been married for a shorter time (Cancian and Meyer 1998;Juby, Le Bourdais and Marcil-Gratton 2005). However, the relationship between shared residence and the parents' marriage is less clear, although some studies suggest that non-resident fathers who were formally married to the child's mother spend more time with them after break-up than those who were cohabiting (Cooksey and Craig 1998). In Norway, Jensen andClausen (1997, 1999) found that, on average, previously cohabiting non-resident fathers spent less time with their children than those who had been formally married, while Skevik (2006) discovered no such association and concluded that cohabitation appears to bind men to their children as much as marriage does.…”
Section: Previous Researchmentioning
confidence: 87%
See 2 more Smart Citations
“…Some studies indicate that father sole custody is more common among previously married than previously cohabiting parents, and more common among parents who had been married for a long time than those who had been married for a shorter time (Cancian and Meyer 1998;Juby, Le Bourdais and Marcil-Gratton 2005). However, the relationship between shared residence and the parents' marriage is less clear, although some studies suggest that non-resident fathers who were formally married to the child's mother spend more time with them after break-up than those who were cohabiting (Cooksey and Craig 1998). In Norway, Jensen andClausen (1997, 1999) found that, on average, previously cohabiting non-resident fathers spent less time with their children than those who had been formally married, while Skevik (2006) discovered no such association and concluded that cohabitation appears to bind men to their children as much as marriage does.…”
Section: Previous Researchmentioning
confidence: 87%
“…Studies of shared residence and father sole custody also vary in terms of the determinants included in the analyses, depending on the theoretical interest of the researchers and the information available in their data (compare, for instance, Cooksey and Craig 1998;Manning, Steward andSmock 2003, Skevik 2006). However, important factors in many studies include the parents' socioeconomic resources, their former and current family obligations, their health, and also more practical considerations, such as the distance between their homes and the father's work flexibility.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Elles ont montré l'accroissement de la proportion d'enfants qui, de plus en plus tôt dans la vie, voient leurs parents se séparer et qui connaissent par la suite la vie en famille monoparentale et, pour plusieurs, la vie en famille recomposée (Bumpass et Lu, 2000 ;Festy, 1994 ;Marcil-Gratton, 1998). Enfin, elles ont tenté de mesurer les effets de la désinstitutionnalisa-tion et de l'instabilité croissante de la vie conjugale sur les liens et les relations que les pères entretiennent avec leurs enfants (Cooksey et Craig, 1998 ;Le Bourdais, Juby et Marcil-Gratton, 2002). Dans la foulée de ces études, un large champ de recherche qui emprunte à la psychologie, à la sociologie, à l'épidémiologie aussi bien qu'à la démographie a tenté de cerner l'effet des bouleversements de la vie familiale des enfants sur leur développement cognitif et émotionnel.…”
Section: Changements Démographiques Et Trajectoires Fami-lialesunclassified
“…A man's age at the birth of his first child and geographical distance from children also has an impact on their relationship. Cooksey and Craig (1998) found that physical distance from children reduced the frequency of father visits. Also, those fathers staying less than 100 miles from their children were more likely to visit and be more involved in their children's daily activities than those who lived further away.…”
Section: Paternal Caregivingmentioning
confidence: 99%